2005
DOI: 10.1128/jcm.43.4.1989-1991.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Unmodified Starches and Partial Removal of Serum To Improve Granada Medium Stability

Abstract: The use of 1% unmodified rice starch and 1% horse serum instead of 2% soluble starch and 5% serum in Granada medium is described. These components result in a medium of increased stability, preventing spoilage after a few days of storage at room temperature.The detection of orange-red colonies in Granada medium (GM) (5) is an easy way of identifying hemolytic Streptococcus agalactiae (a group B streptococcus [GBS]) in clinical samples (1,3,9,11,15,17,20). Proteose Peptone 3 (BD/Difco, Franklin Lakes, N.J.) (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, if not kept refrigerated the medium deteriorates in a few days (12). We have observed that when media containing folate antagonists (as methotretaxate) are used as transport media and swabs are kept in these media for several hours before starting incubation, the number of GBS CFU nosedives.…”
Section: Liquid Granada Medium For Detection Of Group B Streptococcimentioning
confidence: 99%
“…However, if not kept refrigerated the medium deteriorates in a few days (12). We have observed that when media containing folate antagonists (as methotretaxate) are used as transport media and swabs are kept in these media for several hours before starting incubation, the number of GBS CFU nosedives.…”
Section: Liquid Granada Medium For Detection Of Group B Streptococcimentioning
confidence: 99%
“…Indicator broths could be inoculated directly at the point of care, which would be of particular benefit where laboratories are not accessible 24/7. However, the poor stability of Granada medium, and its derivatives [30,31], is an important obstacle to ensuring the availability of media at the point of care. Antigen detection on incubated LIM broth is an alternative to using complex indicator media, and may be more sensitive, as well as faster, than conventional enrichment culture [32].…”
Section: Bacteriology Of Gbsmentioning
confidence: 99%